A methodology for energy dissipation prediction of the bolt group with non-uniform preload. Issue 2 (February 2023) - Sun, Kepeng; Sun, Qingchao; Zhao, Binbin; Zhang, Yingzhong; Liu, Xuewei
Abstract: The bolted joints exhibit typical nonlinear hysteresis under tangential loading, and the deviations of the preload in the bolt group add to the complexity of the model describing this behavior. In this paper, based on the mechanical analysis of the bolt group, a new methodology for predicting hysteresis behavior under non-uniform preload was proposed. Firstly, based on the moment equilibrium within the framework of material mechanics and the tangential stiffness model of the joint interface, a new coordination equation of displacement and force between the bolted joints was deduced, which could realize the calculation of the bolt group loading curve. Then, the PCOM (Preload Co-Occurrence Matrix) was constructed considering the arrangement of the joints, and the indices related to the spatial distribution of the preload were extracted from PCOM. The results of GCA (Grey Correlation Analysis) showed that the indices of PCOM were closely related to the hysteresis behavior of the bolt group. Finally, the prediction of energy dissipation could be realized by using the indices extracted from PCOM and the SVM(Support Vector Machine) regression model. The prediction results were in good agreement with the simulation and experiment, which verified the validity of the methodology proposed in this paper.